2020
DOI: 10.1177/1591019920946216
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of complex middle cerebral artery aneurysms using TuBridge flow diverters

Abstract: Background The safety and efficacy of the TuBridge flow diverter in treating middle cerebral artery aneurysms remains unknown. In this study, we report our preliminary experience treating complex middle cerebral artery aneurysms using the TuBridge flow diverter. Methods A prospectively maintained database of intracranial aneurysms treated with the TuBridge flow diverter was retrospectively reviewed, and patients with middle cerebral artery aneurysms were included in this study. Demographics, aneurysm features,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…As the final angiographic results of our study showed that the rate of complete occlusion (RROC 1) was 80.0% in the SAC group, which was similar to the main results of the last 10 years (from 70 to 88.9%) ( 15 21 ). In the LSM group, 90.3% of aneurysms in complete occlusion (OKM grade D) was the highest rate compared to the results from other LSM studies [70.0% ( 9 ), 73.7% ( 5 )], even higher than TuBridge flow diverters (50% in OKM grades D and C) ( 22 ) or a meta-analysis of flow-diverting stents (78.7% in complete/near complete occlusion) ( 23 ) in MCA. For complicated aneurysms, the two-stage operation is accepted due to the high risk of rupture during coiling ( 24 ).…”
Section: Discussionmentioning
confidence: 57%
“…As the final angiographic results of our study showed that the rate of complete occlusion (RROC 1) was 80.0% in the SAC group, which was similar to the main results of the last 10 years (from 70 to 88.9%) ( 15 21 ). In the LSM group, 90.3% of aneurysms in complete occlusion (OKM grade D) was the highest rate compared to the results from other LSM studies [70.0% ( 9 ), 73.7% ( 5 )], even higher than TuBridge flow diverters (50% in OKM grades D and C) ( 22 ) or a meta-analysis of flow-diverting stents (78.7% in complete/near complete occlusion) ( 23 ) in MCA. For complicated aneurysms, the two-stage operation is accepted due to the high risk of rupture during coiling ( 24 ).…”
Section: Discussionmentioning
confidence: 57%
“…Only 4 subjects with posterior circulation aneurysms were included in this study and were not discussed in detail. Subsequently, the application of Tubridge has been reported in other different subtypes, such as recurrent aneurysms, middle cerebral artery aneurysms, and cavernous carotid artery aneurysms ( 17 , 25 , 26 ). The safety and the efficacy of using Tubridge in BA aneurysms have not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Their conclusion was that telescoping flow diverters showed low perioperative complications and high aneurysm occlusion rate when treating complex intracranial aneurysms. Liang et al [ 13 ] reported the treatment of 8 complex middle cerebral artery aneurysms using the Tubridge device, with no intra-procedural complications, no morbidity or mortality at a mean follow-up of 11.3 ± 3.6 months, suggesting safety and efficacy of endovascular treatment of the middle cerebral artery aneurysms using the Tubridge flow diverter. Because the Tubridge device is still at the initial stage of clinical application, most studies are only composed of a small series of patients as demonstrated in the above studies.…”
Section: Discussionmentioning
confidence: 99%
“…The device has platinum-iridium radiopaque microfilaments which can improve visualization of the device during endovascular treatment. [11][12][13][14][15] The PARAT clinical trial investigating the clinical effect of the Tubridge device in managing large or giant unruptured cerebral aneurysms in multiple centers reported a 75.34% rate of complete aneurysm occlusion at 6 months of follow-up, which was significantly greater than that for stent-assisted coiling (24.53%). [11] The Tubridge device has different design concept, releasing manner, and sizes, and it may have different endovascular performance in treating intracranial aneurysms compaed with other flow diverting devices.…”
Section: Introductionmentioning
confidence: 99%